SPE/IADC Middle East Drilling Technology Conference 2001
DOI: 10.2118/72290-ms
|View full text |Cite
|
Sign up to set email alerts
|

Drilling Fluids Design and Management for Extended Reach Drilling

Abstract: This paper focuses on the potential problems facing the operator in extended reach exploration and development drilling. A practical review is presented of world-wide extended reach drilling fluid experience with examples of successful technology application from specific projects. Critical drilling fluid success factors in the planning and construction of an extended reach well include borehole stabilisation, hole cleaning, lubricity and equivalent circulating density (ECD) management. The latest techniques i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…Because the exploration and production of shale gas have been moving to greater depths under-ground, there is an increasing demand for OBMs that are stable at the high pressures and temperatures (HPHT) encountered at those depths (Cameron, 2001;Young et al, 2006). OBMs is a non-aqueous fluid (NAF) system that offers great benefits to drilling through high lubricity and low friction coefficients, superior shale stabilization, excellent fluid loss control, ensure adequate cooling of the drill string, low bit-balling tendency and high associated rate-of-penetration (ROP), etc.…”
Section: Introductionmentioning
confidence: 99%
“…Because the exploration and production of shale gas have been moving to greater depths under-ground, there is an increasing demand for OBMs that are stable at the high pressures and temperatures (HPHT) encountered at those depths (Cameron, 2001;Young et al, 2006). OBMs is a non-aqueous fluid (NAF) system that offers great benefits to drilling through high lubricity and low friction coefficients, superior shale stabilization, excellent fluid loss control, ensure adequate cooling of the drill string, low bit-balling tendency and high associated rate-of-penetration (ROP), etc.…”
Section: Introductionmentioning
confidence: 99%
“…It is imperative to note that deviating a well horizontally or directionally while drilling is always a solution to bypass the obstructions on the drilling pathway to reach the desired or targeted zone for the economic exploitation of oil and gas reserves but the importance of cleaning a vertical well cannot be overemphasized (Cameron, 2001;Ali et al, 2012). Savin (1985) showed that the unbearable effects of high flow velocities can be overcome by injecting in the the annulus, a slug or slugs in their series with a shear thickening time.…”
Section: Introductionmentioning
confidence: 99%
“…Among important variables for optimizing well cleaning (Cameron, 2001) are hydraulic pressures, pressure drops, rheological properties, and efficiency in transporting solids. The so-called sliding speed, a parameter related to the cleaning of the well, reduces significantly with the increase of the mud flow, so that there is an increase of the cuttings transport (Lim & Chukwu, 1996).…”
Section: Introductionmentioning
confidence: 99%